Intraseasonal Dynamical Evolution of the Northern Annular Mode - McDaniel, Brent (Georgia Institute of Technology, 2005)
Recent observational and modeling studies indicate a robust dynamical coupling between the stratosphere and troposphere during boreal winter. This coupling occurs in association with the Northern Annular Mode (NAM), which itself accounts for a significant fraction of the variability of the extratropical circulation. While monthly NAM dynamics have been studied previously, the mechanisms that give rise to NAM variability on short intraseasonal timescale are still unclear. We perform regression analyses, case studies, and composites based on periods of dynamical growth/decay to investigate the roles of the different proposed mechanisms in driving the atmospheric variability observed in association with the NAM on short intraseasonal timescales. More specifically, lag-regression analyses are used to identify the mean canonical structures present during the evolution of a typical NAM event. Illustrative case studies of robust stratospheric NAM events but with different tropospheric signals are contrasted in order to identify the underlying dynamical reasons for the observed differences. Finally, composite analyses of NAM tendencies are performed to isolate the structural and dynamical evolution of NAM events. Zonal-mean and three-dimensional eddy-flux diagnoses are used to examine the role of eddy-mean flow interaction in driving the wind tendencies characteristic of the NAM. In particular, Plumb flux analyses are employed to quantify the contribution of regional stationary wave anomalies toward the zonal mean wind tendency field. Potential vorticity inversions are also used to determine the role of stratospheric anomalies in inducing tropospheric circulations. The case study analyses indicate that preexisting tropospheric PV anomalies can mask the downward penetration of an initial stratospheric NAM signal into the troposphere. PV inversions further suggest that a minimum requirement for a direct downward stratospheric influence is that the stratospheric NAM signal be robust in the lower stratosphere. The dynamical ...